What Drives Biodiversity Conservation Effort in the Developing World? An analysis for Sub-Saharan Africa - (:unkn) unknown (My University, 2012)
Biodiversity conservation in low-income economies is a vital issue and hence needs to be addressed for development and poverty eradication. A variety of empirical works exist on the subject, but the focus is often limited on the search for possible causes of biodiversity erosion. Research on the "driving forces" that influence biodiversity conservation effort is still largely missing, especially for developing countries. In this study, we seek to address this gap. We test, using different models, the impact of some domestic and external factors on countries' conservation effort measured by the Ecoregion score. We examine specifically whether strategic interactions matter in conservation policymaking at the country level. The model is tested on a data set comprising 48 sub-Saharan African countries spanning over the period 1990-2009. Through the obtained results, we give empirical evidence that, in the context of underdevelopment especially in Sub-Saharan Africa, strengthening governance is an effective mean to support the promotion of biodiversity conservation. In addition, we find that countries in Sub-Saharan Africa are inﬂuenced by their contiguous neighbors in environmental policy for biodiversity management. Finally, the results suggest that tourism development is a valuable incentive to raise governments' dedication to conservation in Sub-Saharan Africa.
Keywords: African Research